Strategic management model for social enterprises based on success factors and fuzzy logic - Moreno Hernández, María Azucena (2025)
The field of social entrepreneurship allows for extensive research for academics as the dual mission they face shows challenges in management and organizational structure.  On the other hand, compensatory fuzzy logic allows representing and evaluating proposals that have been developed by experts in the literature, as well as their valuations in resources and capabilities that such enterprises need to evolve and achieve adequate performance to ensure their survival. This research proposes a strategic management model for social enterprises based on critical success factors and compensatory fuzzy logic elements. With a PRISMA review of the literature, it was possible to extract the critical success factors, which were subsequently validated by experts. Using compensatory fuzzy logic, linguistic predicates were created and modeling was performed with Eureka Universe software. An administrative management model was obtained through knowledge engineering, which was implemented in Libérate Laguna, A. C., an organization focused on mental health.